Wind Energy in Indonesia: Current Status, Potential, Challenge, Opportunities, and Future Policy - Danur Lambang Pristiandaru; Nugroho Agung Pambudi (Indonesian Journal of Energy, 2019)
Like many countries, an increase in population and economic growth has made Indonesia’s energy demands significantly raise. By 2050, Indonesia hopes to have 31% of its energy supply met by tapping on renewable energy, like the wind which can yield up to 16.7% of the power. However, the development of wind energy in Indonesia is still low. One underlying reason is the average speed of wind in Indonesia quite low, making it very difficult to produce energy on a large scale. Many of Indonesia’s current wind energy systems installed in remote locations, often as part of a development or research project in stand-alone or hybrid systems. These partly caused by a lack of confidence in wind power and not being sure of where could be the best locations for wind plants. This paper studies the status of wind energy in Indonesia, the challenges that it faces and future policies.